Choices of immediate open access and the relationship to journal ranking and publish-and-read deals - Wenaas, Lars (Frontiers in Research Metrics and Analytics, 2022)
With the role of academic journals in the reward system of science, their rank can be important for the researcher’s choice in deciding where to submit. The study asks how choices of immediate gold and hybrid open access are related to journal ranking and how the uptake of immediate open access is affected by transformative publish-and-read deals, pushed by recent science policy. Data consists of 186,621 articles published with a Norwegian affiliation in the period 2013–2021, all of which were published in journals ranked in a National specific ranking, on one of two levels according to their importance, prestige, and perceived quality within a discipline. Results are that researchers chose to have their articles published as hybrid twice as often in journals on the most prestigious level compared with journals on the normal level. The opposite effect was found with gold open access where publishing on the normal level was chosen three times more than on the high level. This can be explained by the absence of highly ranked gold open access journals in many disciplines. With the introduction of publish-and-read deals, hybrid open access has boosted and become a popular choice enabling the researcher to publish open access in legacy journals. The results confirm the position of journals in the reward system of science and should inform policymakers about the effects of transformative arrangements and their costs against the overall level of open access.